Implementasi SIPENA: Platform Kecerdasan Buatan untuk Otomasi Perangkat Pembelajaran Bermuatan Literasi-Numerasi bagi Guru SMP - Asri Wahyuni; Monita Dwiyani; Marwah Nur Siti Nadhipah; Galih Pamungkas; Himatul Islamiati; Windi Nurfaujiah Mujib (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
The administrative demands of the Merdeka Curriculum have placed a significant burden on teachers, particularly in preparing comprehensive learning tools, including annual programs (Prota), semester programs (Promes), teaching modules, student worksheets (LKPD), and assessment instruments. This community service activity aimed to examine the implementation of SIPENA (Sistem Perangkat Pembelajaran), an AI-integrated, web-based platform designed to automate administrative tasks for mathematics teachers at SMP Islam Ibnu Hanbal Tasikmalaya. The activity was conducted in two sessions on March 2 and 6, 2026, with 16 teachers and school staff participating. Data were collected through pre- and post-training surveys using a Likert-scale questionnaire, with 14 respondents in the pre-training survey and 8 in the post-training survey. Results showed a notable increase in teachers' understanding of learning administration preparation, from a mean score of 3.71 to 4.50 out of 5 (an improvement of 21.2%). Participants rated both the trainer's presentation quality and the facility's quality at 4.88 out of 5. All survey respondents expressed their intention to apply SIPENA in their teaching practice. These findings indicate that SIPENA is effective in improving teachers' pedagogical competence and administrative efficiency in the digital era.